The Vibrio cholerae var regulon encodes a metallo-beta-lactamase and an antibiotic efflux pump, which are regulated by VarR, a LysRtype transcription factor - Lin, Hong-Ting Victor (2017)
The genome sequence of V. cholerae O1 Biovar Eltor strain N16961 has revealed a putative antibiotic resistance (var) regulon that is predicted to encode a transcriptional activator (VarR), which is divergently transcribed relative to the putative resistance genes for both a metallo-beta-lactamase (VarG) and an antibiotic efflux-pump (VarABCDEF). We sought to test whether these genes could confer antibiotic resistance and are organised as a regulon under the control of VarR. VarG was overexpressed and purified and shown to have beta-lactamase activity against penicillins, cephalosporins and carbapenems, having the highest activity against meropenem. The expression of VarABCDEF in the Escherichia coli (Delta acrAB) strain KAM3 conferred resistance to a range of drugs, but most significant resistance was to the macrolide spiramycin. A gel-shift analysis was used to determine if VarR bound to the promoter regions of the resistance genes. Consistent with the regulation of these resistance genes, VarR binds to three distinct intergenic regions, varRG, varGA and varBC located upstream and adjacent to varG, varA and varC, respectively. VarR can act as a repressor at the varRG promoter region whilst this repression was relieved upon addition of beta-lactams, these did not dissociate the VarR/varRG-DNA complex, indicating that the derepression of varR by beta-lactams is indirect. Considering that the genomic arrangement of VarR-VarG is strikingly similar to that of AmpR-AmpC system, it is possible that V. cholerae has evolved a system for resistance to the newer beta-lactams that would prove more beneficial to the bacterium in light of current selective pressures.